Dream architecture : today's designs for tomorrow - Xing, Rihan (Stuttgart : Edition Axel Menges, 2010)
As building materials and technologies advance, architects are creating new kinds of urban environments. Among the innovations showcased in this book that are contributing to new architectural forms are parametric modeling enabled by computer-aided technology, environmentally friendly building skins, and HOPSCAs - a hybrid building type - that can house hotels, offices, parking, shopping, a convention center, and apartments under one roof. The dream buildings in this book reflect a changing architectural and cultural environment, and the processes that turn these concepts from vision to reality will open a new chapter in architectural history.
Keywords: Architecture, Modern -- 21st century